Co-existing with the Other in the Aspect of the Problem of Fluctuations of Personality in the Society - Petinova, Oksana; Tkachenko, Ekaterina (Studia Warmińskie, 2022)
In this article an analysis of the concept of the Other in the context of the issue of “I and the Other” is introduced, and the ways through which the process of identification of personality within the framework of coexistence with the Other are shown within the context of phenomenological philosophy. The problem of identification is analysed as an integral part of the problem of the Other, since an individual always acts within the horizon of the intersubjective heritage. A person is born in a certain cultural tradition, without the intersubjective dimension of which their self-identification is impossible. A person is born in a world which is already imbued with the meanings of others, therefore, there always exists a need for their self-identification, which cannot be done without active participation of the Other. The processes of globalization, informatisation and post-industrialisation indicate that in the modern world social reality is constructed through brand-new algorithms, which cannot but impact the processes of socialization and self-identification, and lead to personality’s deep changes, which are made evident by its fluctuations.